A Time to be born and a time to die - Kogan, Barry S (Aldine De Gruyter, 1991)
Revised versions of papers presented at a conference on ethics, held on Oct. 15-17, 1989 in Cincinnati, Ohio, sponsored by the Hebrew Union College-Jewish Institute of Religion through its Starkoff Institute of Ethics and Contemporary Moral Problems.; Includes bibliographical references and index.; Neal A. Newfield, Ph.D., LICSW (Giver)